The role of student engagement in the relationship between classroom motivation and academic achievement / Shailaja Damodaran - Shailaja , Damodaran (2020)
The aim of this study was to investigate undergraduate students’ perceived classroom motivation and perceived engagement in learning English course. It also examined the extent to which student engagement plays a mediating role in the relationship between classroom motivation and academic achievement. Using the Basic Needs Satisfaction at College Scale (Jenkins-Guarnieri et al., 2015) and Student Course Engagement Questionnaire (Handelsman et al., 2005), cross sectional surveys were conducted to collect data on classroom motivation and student engagement, respectively. Academic achievement was measured based on students’ course examination results. The sample comprised 137 undergraduate students from a public university in Malaysia. Data was analyzed using Statistical Package for the Social Sciences (SPSS) 22 and Structural Equation Modelling with SMART PLS 3. The findings showed that student engagement not only has direct relation to academic achievement, but also mediates the influence of classroom motivation on academic achievement. The results of this study encourage instructors to fulfil students’ intrinsic motivational needs in order to foster authentic engagement in learning, which in turn leads to improved academic gains. Limitation of this research is that the finding is only relevant to a specific class investigated during the time of study and the findings cannot be generalized to a larger population due to low number of participants. Future research may attempt to conduct longitudinal study to observe students’ motivation and engagement pattern throughout a semester and whether their level of motivation and engagement change over time.